Vascular Pathology Causing Late Onset Generalized Chorea: A Clinico‐Pathological Case Report. Issue 6 (8th September 2017) - Salgado, Paula; Taipa, Ricardo; Domingos, Joana; Dias, Daniel; Pires, Manuel Melo; Magalhães, Marina
Abstract: Background: Chorea may occur as a manifestation of an acute stroke. Patients with vascular‐related chorea typically present with an acute or subacute onset of hemichorea, contralateral to the lesion. Methods and Findings: In this clinico‐pathological case, we report a 90‐year‐old female who presented, at age 81, with a transient episode of generalized chorea. Over the years, the patient continued to have intermittent episodes of generalized chorea or hemichorea, followed by a progressive dementia syndrome with gait and sphincter disturbance. There was no family history of chorea or dementia. Laboratory tests for paraneoplastic or autoimmune disorders and genetic testing for Huntington's disease were normal or negative. Magnetic resonance imaging showed subcortical and basal ganglia atrophy associated with ischemic leukoencephalopathy and lacunar infarcts. The post‐mortem examination identified multiple lacunar infarcts (cortex, white matter, thalamus, basal ganglia) and minor Alzheimer′s disease neuropathological changes. Conclusions: Vascular disease, affecting the basal ganglia, is included in most lists of causes of generalized chorea. Proven cases are difficult to find. We present a rare case of vascular pathology causing late onset generalized and intermittent chorea. We highlight the intermittent nature of the chorea that could be explained by cumulative vascular lesions or functional disconnection in a previous deficient circuit.